Fire hazards in heritage villages: A case study on Dangjia Village in China. (June 2018) - Yuan, Chunyan; He, Yaping; Feng, Yingbin; Wang, Pengfei
Abstract: Fire protection for heritage villages is a complex issue involving multiple factors, especially for heritage villages comprising brick–timber framed buildings. This study aims to investigate fire hazards in heritage villages and to provide an assessment on fire safety. Site investigations were conducted in a heritage village with data collections in terms of four aspects. First, brick wall condition was investigated. Second, the integrity of timber columns was inspected with the measured wood moisture content. Third, the accessibility of fire brigade intervention and active firefighting facilities was assessed. Finally, other fire hazards, such as disordered electrical wiring, were identified. A linear additive model with multiple attribute evaluation was then used to produce a measure of relative fire hazards. This study revealed significant structural deteriorations in the surveyed heritage village. Several identified fire hazard factors were quantified. Specifically, most external columns suffered different types of damage or erosion, and only 26% of the columns remained intact. The average surface moisture content of timber columns was 12.7% with a standard deviation of 5.95%. Only 10% of the roadways in the village were accessible for fire trucks. A single numerical assessment value represented that the fire safety level in the heritage village was low. The study provided actual information for the development of systematic approach and performance-based design on fire protection in heritage villages.